Clinical-Pathological Correlation of Breast Non-mass Enhancing Lesions. (9th November 2022) - Huang, W; Han, B
Abstract: Introduction/Objective: MRI imaging of breast is mainly reserved for screening high-risk individuals with occasional application in women bearing moderate or average risk. Areas showing enhancement in MRI without space-occupying mass are defined as non-mass enhancement (NME). As biopsy of NME lesion is rare encounter in clinical practice, thorough clinical-pathological investigation is warranted. Methods/Case Report: 289 patients who underwent core biopsy for NME lesion(s) in our institution between 2011 to 2021 were included in this retrospective study. Pathological diagnoses were lumped into 3 categories, namely benign, precursor lesions (atypical ductal hyperplasia, atypical lobular hyperplasia, and lobular carcinoma in situ), and malignant lesions (ductal carcinoma in situ, pleomorphic lobular carcinoma in situ, and invasive carcinoma). The age distribution, MRI indications, and pathological diagnoses stratified by indications were studied. MRI patterns of NME lesions were compared between malignant versus benign lesions. Results (if a Case Study enter NA): Patient's age ranges 25-79 yo (mean age 51.9 yo, median age 50 yo). Indications of MRI include high-risk screening (162 cases, 162/289, 56%), pre-operative staging (116 cases, 116/289, 40%), and problem-solving (11 cases, 11/289, 4%). There are 220 benign cases (220/289, 76%), 50 malignant cases (50/289, 17%), and 19 precursor lesions (19/289, 7%) in this study. There were 16 malignant cases identified in the high-risk group (16/162, 10%), 24 in the pre-operative staging group (24/116, 20.7%), and 2 in problem-solving group (2/11, 18.2%). Focal distribution is significantly associated with malignant lesions as compared to other patterns (linear, segmental, and regional) (Chi-square test, p<0.001). Conclusion: High-risk screening is the major indication for biopsy NME lesions, followed by pre-operative staging, and problem-solving. Benign lesions are the predominant pathological findings of NME lesions, followed by malignant and then precursor lesions. Malignant lesions were mostly identified in high-risk group, followed by pre-operative staging and problem-solving group. Malignant lesions tend to assume the "focal distribution" than other MRI patterns.